Bone turnover markers to assess jawbone quality prior to dental implant treatment: a case-control study - Keisuke Yasuda; Shinsuke Okada; Yohei Okazaki; Kyou Hiasa; Kazuhiro Tsuga; Yasuhiko Abe (International Journal of Implant Dentistry, 2020)
Abstract Background Bone quality is as important as bone mineral density in terms of bone strength. Bone turnover markers (BTMs) are clinical indicators of bone quality. In implant dentistry, bone quality is considered equivalent to bone density on radiographic assessments. The purpose of this study was to determine whether the BTM values are reflected in jawbone condition by evaluating the relationship at baseline and during follow-up in patients with prosthodontic implants. Computed tomography (CT) scans were obtained and BTM (osteocalcin, bone-specific alkaline phosphatase, pyridinoline cross-linked carboxyterminal telopeptide of type I collagen, and crosslinked N-telopeptide of type I collagen) levels in blood samples were measured in partially edentulous eighteen patients before implant surgery. During the follow-up observation after implant surgery, marginal bone loss (MBL) was measured on dental radiography. We investigated the relationship between the presence of BTM abnormalities and radiographic bone density. Results More women than men had abnormal BTM values. Bone turnover was accelerated in the group of women with abnormal BTM values. The density of cancellous bone at the implant placement site was significantly lower in the patients with abnormally high BTM values than in their counterparts with BTM values in the normal range. Conclusions Female patients who undergo implant treatments may have reduced bone quality; evaluations of bone strength will require assessments of both BTMs and the density of cancellous bone.